Re-Layout Tata Letak Fasilitas Produksi Sepatu Menggunakan Metode Systematic Layout Planning dan Blocplan - Muhammad Andriyanto; Atikha Sidhi Cahyana (G-Tech: Jurnal Teknologi Terapan, 2024)
PT Inti Dragon Suryatama is engaged in the shoe and sandal manufacturing industry. Judging from the workstations and the placement of machines that are 3 to 5 metres apart, even though only a few people pass through, thus causing interference with the flow of the process because it takes a long time, so that the production site is not optimal. In the production department there is also a buildup of materials, moving materials too far from the production area to the packing department. This research aims to reduce the distance between departments. The method that will be used to redesign the factory layout is the systematic layout planning (SLP) method and blocplan. The results of this study obtained a change in distance in the proximity of each department, the initial distance of 45.7 metres to 33.5 metres, then the efficiency of using the blocplan algorithm is 26%.